2006
DOI: 10.1021/bi060289i
|View full text |Cite
|
Sign up to set email alerts
|

Localizing α-Helices in Human Tropoelastin:  Assembly of the Elastin “Puzzle”

Abstract: Polyalanine cross-linking domains encoded by exons 6, 15, 17, 19, 21, 23, 25, 27, 29, 31 of human tropoelastin were synthesized, and their conformations were studied in different solutions and at different temperatures by CD and (1)H NMR. The results demonstrated the presence of poly-proline II helix (PPII) in aqueous solvent and of alpha-helical conformation in TFE. The (1)H NMR results allowed the precise localization of the helices along the peptide sequence. These data were further refined by prediction al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
96
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(106 citation statements)
references
References 57 publications
9
96
0
1
Order By: Relevance
“…Observed helical content, measured by CD or NMR, is consistently lower than would be expected for fully formed helical structures (4,16,17,35). Indeed, fully formed ␣-helices were only observed on the addition of known helixinducing solvents such as trifluoroethanol (TFE) 2 (4,16). Thus, it remains unclear whether interaction of lysine side chains in the cross-linking domains is entirely dependent on alignment of hydrophobic domains or may be the result of stochastic fluctuations in structure that lead to juxtaposition of lysine side chains.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Observed helical content, measured by CD or NMR, is consistently lower than would be expected for fully formed helical structures (4,16,17,35). Indeed, fully formed ␣-helices were only observed on the addition of known helixinducing solvents such as trifluoroethanol (TFE) 2 (4,16). Thus, it remains unclear whether interaction of lysine side chains in the cross-linking domains is entirely dependent on alignment of hydrophobic domains or may be the result of stochastic fluctuations in structure that lead to juxtaposition of lysine side chains.…”
mentioning
confidence: 84%
“…Observed helical content, measured by CD or NMR, is consistently lower than would be expected for fully formed helical structures (4,16,17,35). Indeed, fully formed ␣-helices were only observed on the addition of known helixinducing solvents such as trifluoroethanol (TFE) 2 (4,16).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The atomic coordinates for the 15 best of 100 NMR conformers of pHTE 27 was generously provided by Antonietta Pepe and Brigida Bochicchio (35). The lowest root mean standard deviation pHTE 27 NMR structure from the set of 15 was used for docking.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 Polyalanine cross-link domains, encoded by several exons of human tropoelastin, exhibited poly-proline II helix and a-helix conformation in aqueous and trifluoroethanol solutions, respectively. 17 Several NMR dynamic studies have also pointed to elastin being highly mobile with the association of water. [18][19][20] The NMR relaxation times of waters of hydration in elastin have been studied, and it was suggested that two distinct water components exist within elastin fibers; tightly bound waters of hydration in addition to water having more ''bulk-like'' properties reminiscent of free water.…”
mentioning
confidence: 99%